2017
DOI: 10.1542/peds.2017-1305
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Type 1 Diabetes and Celiac Disease Autoimmunity

Abstract: BACKGROUND AND OBJECTIVES Few birth cohorts have prospectively followed development of type 1 diabetes (T1D) and celiac disease (CD) autoimmunities to determine timing, extent of co-occurrence, and associated genetic and demographic factors. METHODS In this prospective birth cohort study, 8676 children at high genetic risk of both diseases were enrolled and 5891 analyzed in median follow-up of 66 months. Along with demographic factors and HLA-DR-DQ, genotypes for HLA-DPB1 and 5 non-HLA loci conferring risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 48 publications
3
69
2
Order By: Relevance
“…There are preclinical studies demonstrating that a gluten-free diet prevents or delays diabetes onset in nonobese diabetic mice, 13 and changes the composition of the innate immune system, 14 which is in contrast to results reported by Hagopian et al 10 in which autoimmunity to CD was not significantly associated with development of T1D autoimmunity. Two clinical trials have been conducted to evaluate the relationship between gluten exposure and T1D.…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…There are preclinical studies demonstrating that a gluten-free diet prevents or delays diabetes onset in nonobese diabetic mice, 13 and changes the composition of the innate immune system, 14 which is in contrast to results reported by Hagopian et al 10 in which autoimmunity to CD was not significantly associated with development of T1D autoimmunity. Two clinical trials have been conducted to evaluate the relationship between gluten exposure and T1D.…”
contrasting
confidence: 62%
“…In this issue, Hagopian et al 10 find that the co-occurrence of T1D autoimmunity and CD autoimmunity is higher than would be expected in the general population. In a crosssectional analysis, individuals with autoantibodies to 1 disease had increased prevalence of antibodies to the other disease.…”
mentioning
confidence: 88%
“…Our finding of increased risk of CD with younger-onset diabetes is in agreement with previous studies of children with diabetes. 2,12,13,15 The mechanism underlying increased risk of CD with younger age at diabetes diagnosis may be related to the hypothesis of common determinants for both diseases, 13 including environmental exposures, genetic background (including HLA and non-HLA variants), 31,32 and the gut microbiome. 33 Combined exposure history and genetic predisposition may impact autoimmunity: for example, timing of cereal introduction to infants genetically susceptible to diabetes or CD is associated with seropositivity, and certain viral infections have been linked to diabetes and CD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Further unanswered questions are the right age for the first screening to optimise diagnostic yield and prevent permanent complications and how seronegative cases should be followed up. Interestingly, evidence provided by The Environmental Determinants of Diabetes in the Young, a prospective multicentre birth cohort study published in 2017, indicated that the great majority of genetically at‐risk children developed coeliac disease autoantibodies before 10 years of age . However, this may not be generalisable to all populations and it must be realised that new cases of celiac disease can appear at any age.…”
Section: Different Approaches To Identify Coeliac Diseasementioning
confidence: 99%